Examining the relationship between foreign language anxiety and foreign language enjoyment from the perspective of positive psychology - Yu, Qiangfu (Frontiers in Psychology, 2025)
Negative emotions represented by foreign language anxiety (FLA) have long been an important topic in the study of second language acquisition (SLA), while the influence of positive emotions on foreign language learning (FLL) has long been neglected. Since Positive Psychology (PP) was introduced into the field of SLA, research on learners’ positive and negative emotions in SLA based on the perspective of PP has begun to flourish. Particularly, the correlation between foreign language enjoyment (FLE) and FLA has become a hot topic. Based on the analysis of the literature on FLA and FLE, it was found that the research on FLA and FLE mainly focuses on the following categories: correlation between FLA and FLE, influencing factors of FLA and FLE, correlation of FLA and FLE with academic achievements, and dynamicity of FLA and FLE. This study summarized the major findings in the four research hotspots and concluded with some research lacunae and possible directions for future research on FLA and FLE from the perspective of PP.